MOTIVATIONAL FACTORS AND USER AWARENESS IN PATIENTS USING SKIN LIGHTENING CREAMS REPORTING TO DERMATOLOGY OUT PATIENT DEPARTMENT IN COMBINED MILITARY HOSPITAL RAWALPINDI - Malik, Sakina Sadiq; Mashhood, Asher Ahmed; Tahir, Moizza; Minhas, Irfan Jamil; Sadiq, Sunniya (Pakistan Armed Forces Medical Journal, 2021)
Objective: To check the motivational factors behind the usage of skin lightening creams and users’ awareness in our setup by constructing a validated questionnaire. Study Design: Cross-sectional study. Place and Duration of Study: Outpatient Department of Dermatology, Combined Military Hospital Rawalpindi, from Oct to Nov 2020. Methodology: Two fifty patients who were using skin-lightening creams (SLC) were recruited after the informed consent. Questionnaire was made following seven steps as mentioned in AMEE (Association for Medical Education Europe) guide 87. Data was analyzed by SPSS version 21. Reliability was be checked by Cronbach@. Descriptive statistics of responses including frequencies and percentages were calculated. Exploratory factor analysis of questionnaire was made. Results: Skin lightening cream users had age range from 16-56 years, majority 190 (76%) were females. Out of 158 (63.2%) were married, 180 (72%) well educated and 146 (58.4%) had Fitzpatrick skin type 3-5 predominate. Cronbach alpha of our questionnaire was 0.802. The 5-point likert scale was used to record users’ perceptions in the domains i.e., motivational factors, awareness about product and intentions. Majority, 89 (35.6%) used the product on social media recommendation. Out of 201 (80.4%) developed side effects with telangiectasia and skin thinning being the commonest ones. Out of 88 (35.2%) were using other skin whitening practices besides these creams. Conclusion: False perceptions about fairness and lack of user’s awareness govern the skin lightening practices in our society resulting in increased usage and side effects experienced by users. A mass educational awareness program regarding “skin lightening.........